BACTERIAL BLIGHT AND MOSAIC DISEASE DETECTION ON CASSAVA LEAF USING SUPPORT VECTOR MACHINE - Hajar Izzati Mohd Ghazalli; Nor Atiqah Roslan (Journal of Islamic, Social, Economics and Development, 2022)
Cassava has been used as a staple food of many nations. It is also known as manioc,and tapioca. In Malaysia, cassava is eaten as supplementary food either steamed, boiled orfried and small cottage industries produce traditional snacks. Its tuber is the most popular formof consumption, although the leaves are also consumed at times for medicinal purposes. Eventhough cassava is a popular form of consumption, it is vulnerable to disease. The type of diseasethat can be found on cassava is bacterial blight and mosaic disease. Problems arise whenfarmers must detect the disease using the expert's naked eyes which takes a lot of time and is adifficult process to be carried out on a large farm and it may lead to inaccurate results. Hence,we proposed work that includes applying techniques of image processing to automaticallyclassify cassava leaf into mosaic and bacterial blight disease. Features such as color andtexture are obtained from the leaf image and Support Vector Machine (SVM) are used toclassify the cassava leaf. It is found that SVM gives of 87.5% accuracy. Therefore, SVM is foundeffective in detecting cassava leaf diseases.